Preliminary studies of cryptic species: Phylogenetic Relationship of Cyrtodactylus sp. from Lombok Island using the NADH Dehydrogenase Subunit 2 gene - Devi Sandra Rafika; Eprilurahman Rury; Kurniawan Ali; Agustina; Aisy Yasinta Rohadatul; Adhawati Laela; Kamilaeni; Gusli Tizar (BIO Web of Conferences)
Genus Cyrtodactylus has high morphological diversity, which often leads to confusion in its classification. The geographical history formed from ocean islands and were not separately part of the continental shelf. This research was conducted to confirm the identity of the Cyrtodactylus sp. specimen from Lombok Island using ND2 gene, taken from 5 different locations. Molecular analysis was carried out through the stages of DNA extraction from liver tissue using the NexPrepTM Cell/Tissue DNA Mini Kit, DNA quality testing by electrophoresis, target gene amplification using the Polymerase Chain Reaction method with Primers M112F and M1123R. The reults of alignment are 600 bp, BLAST and phylogenetic analysis results confirmed that three specimens of Cyrtodactylus sp. from Lombok Island are the same species as C. jatnai from Bali Island. Hopefully, this research can help develop similar research and future map conservation strategies for the Cyrtodactylus spp.